Risk factors and most common traumatic injuries in people who practice long-distance running - Anna Lewandowska; Dorota Ratuszek-Sadowska; Jarosław Hoffman; Anetta Hoffman; Monika Kuczma; Leszek Landowski; Wojciech Hagner (Kazimierz Wielki University, 2017)
Undoubtedly, the fashion of running comes. Initially people used to run for fun, pleasure, to forget about worries or problems. With time, however, was no longer just about the idea itself, people more and more fascinated with jogging went one step further. At the same time, not realizing how important changes may occur in their body. These are usually overload or inflammatory changes. The aim of this paper is to present the most frequent injuries of long distance runners and the main predisposing factors for their trauma. The work will also cover the possibility of prevention of these injuries. The most important factors predisposing to injury include: the awareness of running people, the overweight and obesity, the incorrect running pattern and the inappropriate training plan. The consequences of these factors may be: runner's knee, leg overload syndrome, Achilles tendonitis, plantar fasciitis, fatigue fractures, and iliotibial-band syndrome. The injuries are, unfortunately, inscribed into the life of every runner, regardless of the level of advancement. However, it is worth remembering that they can be effectively prevented, and at the moment of their appearance, effectively heal. The injuries of runners depend primarily on their approach to practicing this form of physical activity, to a lesser extent from genetic or mechanical factors.